Evaluasi Perilaku dan Kinerja Struktur Gedung Pelayanan Medis Rumah Sakit RKZ Surabaya Dengan SNI 1726:2019 - heri istiono; Madaret Rifqi Dzakwan (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Updating regulations from SNI 1726 – 2012 to SNI 1726 – 2019 allows evaluation of the behavior and performance of building structures to reduce the risks posed by earthquakes. This is necessary because in SNI 1726-2019 there is an additional long period in the spectrum response so it is necessary to evaluate it to ensure that the building structure whose behavior still meets the requirements in the regulation. The method used in this study was the pushover analysis method. This study evaluates the St. Catholic Hospital Medical Services building. Vincent a. Paul (RKZ) Surabaya. This study discusses building analysis based on SNI 1726 - 2019 to determine the behavior and performance of structures. The results of this study indicate that the behavior of the structure which includes the time period, base shear force, drift ratio, dual system control meets the requirements in accordance with SNI 1726-2019. This performance level is included in the LS (Life Safety) category.